Google search and tools in a snap - Gralla, Preston (Sams teach yourself., 2006)
These days, nobody really wants to learn everything there is about a product like Google Tools. And even if you did, who has the time to endlessly tinker and play with it until you figure everything out? You just want a book that will quickly show you how to do things with Google Tools, like perform power searches, find pictures with Google Images, find online bargains with Froogle, use the Google Toolbar, and discover the world with Google Earth. Google Search and Tools in a Snap does just that. Organized into a series of well-organized, bite-sized, quickly accomplished tasks, the book lets you zero right in on the one particular task you want to accomplish, quickly figure out what to do, do it, and then get back to using the plethora of Google Tools.